Two new species and descriptive notes for five Pseudosinella species (Hexapoda: Collembola: Entomobryidae) from West Virginian (USA) Caves - Soto-Adames, Felipe N. (Zootaxa, 2010)
The present contribution gives a taxonomic account of the members of the springtail genus Pseudosinella Schäffer, collected during the 2004–2006 expeditions organized by Daniel Fong and David Culver to caves of eastern and southern West Virginia. These expeditions are part of an ongoing long-term effort to develop a complete inventory of the cave fauna of the state. The samples examined include seven species of Pseudosinella, two of which, P. josemarii sp. nov. and P. meganporteri sp. nov. are new to science. For five previously named species descriptive notes are given emphasizing new or incompletely described characters such as the dorsal and ventral head chaetotaxy, number of teeth in the ungulum of the maxilla, presence or absence of setae a6 on the first abdominal segment, and lateral chaetotaxy of the fourth abdominal segment. Detailed analysis of the dorsal chaetotaxy of the head shows that Gisin’s RST system of nomenclature confounds the identity of some macrosetae, hence, a new nomenclature system, denominated AMS, is proposed to more consistently identify macrosetae across all Lepidocyrtini. In addition, a system is proposed to describe variation in number of postlabial setae, their shape and ornamentation.